ANALISIS INTERAKSI PENDIDIKAN ANTARA GURU DAN SISWA DALAM PROSES PEMBELAJARAN IPS TERPADU PADA KELAS VIII - Ina, Irena; Noor, Agus Sastrawan; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this thesis is Analysis of Educational Interaction between Teachers and Students in Integrated Social Studies Learning Process in Class VIII D of 18 Siantan Middle School in North Pontianak District. The problem in this study is how the interaction of education between teachers and students of class VIII D in the process of integrated social studies learning at 18 Siantan Junior High School. The results of this study indicate that: 1) educational contacts conducted in the learning process that is the teacher when opening learning activities always give greetings and introductory lessons. But in the implementation of learning the teacher sometimes never gives a smile, looking at students attentively when students do good actions when learning takes place; 2) educational communication in the learning process has not gone well, it can be seen from the teacher in conveying information, explaining, giving motivation and proposing personal opinions that have not been maximally implemented; 3) the normative element of education carried out in the learning process, namely conducting group discussions conducted by the teacher has not been carried out as expected, such as concentration, giving an explanation of various problems in the learning process; 4) i the technical process of education carried out in the learning process is to carry out closing activities carried out by the teacher not yet fully done when the activity is closed such as summarizing / summarizing the core subject matter that has been delivered.Â Keyword : Interaction, Education, Teachers and Students